2020
DOI: 10.24252/kah.v8i2a11
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of the Department of Library Science's Website by WebQual 4.0

Abstract: This research discusses the quality of the website of the Library Science Study Program Universitas Islam Negeri Alauddin Makassar as a medium of information using the WebQual 4.0 method. Three measurement variables are used, namely: Usability Quality, Information Quality, and Interaction Quality. This descriptive study uses a quantitative approach in presenting data. The data were obtained through online questionnaires and website observations. The population in this study was 448,440 the number of website vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
(2 reference statements)
0
0
0
Order By: Relevance
“…The results of this analysis are consistent with those of a study (Ibrahim et al, 2020) that applied the same computational method to WebQual 4.0's dimensions. Ibrahim's research found that usability, interaction, and service interaction quality all scored good average scores.…”
Section: Image 5 Range Of Service Interaction Quality Test Scoresupporting
confidence: 83%
See 3 more Smart Citations
“…The results of this analysis are consistent with those of a study (Ibrahim et al, 2020) that applied the same computational method to WebQual 4.0's dimensions. Ibrahim's research found that usability, interaction, and service interaction quality all scored good average scores.…”
Section: Image 5 Range Of Service Interaction Quality Test Scoresupporting
confidence: 83%
“…Next, evaluate how much of quality of the website based on WebQual 4.0 dimensions using criterion scores to determine the quality of the research results. According to [7], [8], this criterion score can be used to assess data from questionnaires that include a Likert scale and a rating scale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations